2002
DOI: 10.1210/jcem.87.5.8498
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Insulin Secretion and Clearance to Glucose-Induced Insulin Concentration in African-American and Caucasian Children

Abstract: Relative to Caucasians (C), African-American (AA) children and adults have lower indices of insulin sensitivity (S(i)) and a higher acute insulin response to glucose (AIR(g)). Among AA children, AIR(g) is greater than that which would be predicted based on lower S(i). The objectives of the present study were 1) to determine whether insulin secretory parameters differ in AA vs. C children and adolescents using C-peptide modeling, 2) to determine whether hepatic insulin extraction differs with ethnicity/race usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
59
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(70 citation statements)
references
References 33 publications
(35 reference statements)
7
59
2
Order By: Relevance
“…Within the PCOS group, we observed that black women demonstrated higher ␤-cell function than did their white counterparts, although this difference did not reach statistical significance. It is well established within healthy populations that insulin secretion is higher among blacks vs. whites (41,42). It is likely that a larger sample size in the present study would have yielded a significant difference between races in insulin secretion among subjects with PCOS as well.…”
Section: Discussionmentioning
confidence: 77%
“…Within the PCOS group, we observed that black women demonstrated higher ␤-cell function than did their white counterparts, although this difference did not reach statistical significance. It is well established within healthy populations that insulin secretion is higher among blacks vs. whites (41,42). It is likely that a larger sample size in the present study would have yielded a significant difference between races in insulin secretion among subjects with PCOS as well.…”
Section: Discussionmentioning
confidence: 77%
“…29 It is possible that other measures would be able to provide a more detailed assessment of insulin secretory dynamics. Although our research group has previously characterized differences in insulin secretory measures among whites, blacks, and Hispanics using C-peptide modeling, 23 we were unable to perform similar analyses in the present study. C-peptide modeling would help to identify both insulin secretion and clearance and whether differences in these variables are evident during puberty.…”
Section: Insulin Secretionmentioning
confidence: 72%
“…However, insulin secretion and extraction are known to differ by race. Gower and colleagues 23 have shown that AIRg is higher in blacks versus whites, and this may be the result of either increased insulin secretion or decreased insulin clearance. The underlying physiology is still unknown, but group differences may relate to lower hepatic tissue mass or a conservation of b-cell function in blacks.…”
Section: Insulin Secretionmentioning
confidence: 98%
See 1 more Smart Citation
“…[16][17][18][19] These alterations of insulin dynamics can present in the first decade of life before the onset of weight gain 20 and tend to worsen during puberty. 16,21,22 However, despite their insulin resistance, black children paradoxically have greater subcutaneous and less visceral fat, 23 and black adults, for any level of body mass index (BMI), exhibit decreased incidence of the Metabolic Syndrome, both in adults 24 and children.…”
Section: Discussionmentioning
confidence: 99%